(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In electro-hydraulic systems (EHS), when using tach generator feedback, we have high-frequency noise due to various sources. Precise control of the speed of the actuator is necessary because the tachometer signal is crucial for closed-loop control. Therefore, accurate measurements are essential. In this paper, an analysis of Wiener filter and low-pass filters used in an electro-hydraulic system with feedback from the speed of the actuator (hydraulic motor) is made.